Revisitando o romantismo a partir da escrita feminina e negra de Maria Firmina dos Reis - Barcelos, Schayanny Bárbara de Lima (2023)
This research investigates the writing of black female authorship at the end of the 19th century from the novel “Úrsula” by Maria Firmina dos Reis, the first novel written by a woman and the first Brazilian abolitionist novel, from which it proposes to revisit the literary school of Romanticism and insert discussion of ethnic-racial relations in literature, along with their presence in teaching literature in the second year of high school. The Romance by Maria Firmina dos Reis has great historical and literary importance, mainly due to its abolitionist theme which contributes to discussions about race maintained by Law 10.639/03. In order to observe the reception of this novel by EEEFM “Ilda Ferreira da Fonseca Martins” students of the second grade of High School, reading circles and discussion of the work were conducted, as well as literary workshops so that the characteristics of the narrative and of the characters began to be adressed to. The work of Antonio Candido (2000) was used as a theoretical reference in order to understand the formation of Brazilian Literature, as well as to investigate the absence of Maria Firmina dos Reis in the Brazilian literary canon. In addition, a study of the criticism of the novel “Úrsula” was made to understand the importance of this work. So, based upon Cosson's (2006) literary literacy proposal, we structured literary workshops to bring the novel to the classroom. The results indicate that it is possible to introduce the novel by Maria Firmina dos Reis in the teaching of Romanticism in High School in with the purpose of bringing new perspectives to this literary moment from the black characters, as well as it is possible to use the novel “Úrsula” to understand and discuss issues related to race nowadays.